A New Hybrid EDTA–Zirconium Phosphate Cation-Exchanger: Synthesis, Characterization and Adsorption Behaviour for Environmental Monitoring - S.A. Nabi; Mu. Naushad; Rani Bushra (Adsorption Science & Technology)
EDTA–zirconium phosphate has been synthesized as a new amorphous hybrid cation-exchanger by the combination of the inorganic ion-exchanger zirconium phosphate and EDTA, thereby providing a new class of organic–inorganic hybrid ion-exchanger with better mechanical and granular properties, a good ion-exchange capacity (2.40 mequiv/g dry exchanger for Na + ), good reproducibility, and a higher stability and selectivity towards heavy metal ions. It has been characterized using FT-IR, TGA/DTA, X-ray and SEM methods, in addition to ion-exchange studies such as the determination of its ion-exchange capacity, elution and distribution behaviour, to provide a better understanding of the ion-exchange behaviour of the material. On the basis of distribution studies, the material was found to be highly selective towards Th(IV) and its selectivity was examined by achieving some important binary separations such as Cd(II)–Th(IV), Ni(II)–Th(IV), Hg(II)–Th(IV), Zn(II)–Th(IV), Pb(II)–Th(IV) and Al(III)–Th(IV) by column means, indicating its utility in environmental pollution control in one way or other.